USULAN PERANCANGAN TATA LETAK PENEMPATAN BARANG JADI DI WAREHOUSE MENGGUNAKAN METODE ABC DI PT ELKEN GLOBAL INDONESIA - Dede Rukmayadi; Ade Dulkarim; Muhammad Kholil (Institut Sains dan Teknologi Al-Kamal, 2022)
PT MLM is a company engaged in Multi-Level Marketing and is the main distributor. With a large demand for goods increasing the number of products that must be stored in the warehouse, warehouse management, especially the placement of finished goods, is needed to overcome the impact of the limited warehouse area with the increasing number of finished goods that must be stored. The ABC method is used in this study in the hope that it can propose a warehouse layout arrangement for the placement of finished goods and propose a system for placing and retrieving finished goods. From the results of data processing, it was obtained class A classifications of 7 items with a value of 79.3% which represented 5.8% of the total finished product, class B as many as 13 items with a value of 14.8% representing 10.7% of the total finished product, and class C as many as 101 items with a value of 5.9% representing 83.5% of finished products. From the proposed layout, it gives efficiency values from several sides, namely the search side of 4.00%, the packing side of 2.01%, and the placement side of 7.06%.